Cell‐Penetrating Chaperone Peptide Prevents Protein Aggregation and Protects against Cell Apoptosis. Issue 1 (13th November 2017) - Raju, Murugesan; Santhoshkumar, Puttur; Sharma, K. Krishna
Abstract: Many of the newly discovered therapeutic peptides and molecules are limited by their inability to cross the cell membrane. In the present study, a cell‐penetrating peptide (CPP), VPTLK, derived from Ku70 protein, is employed to facilitate the entry of a minichaperone across the cell membrane. Previous studies suggest that the minichaperone peptide representing the chaperone site in αA‐crystallin, which can inhibit protein aggregation associated with proteopathies, has therapeutic potential. A synthetic minichaperone is prepared by fusing the VPTLK sequence to N‐terminus of minichaperone (FVIFLDVKHFSPEDLTVKGRD) to get VPTLKFVIFLDVKHFSPEDLTVKGRD peptide, which is called "CPPGRD." The amino acids, glycine–arginine–aspartic acid (GRD), are added to increase the solubility of the peptide. The chaperone‐like function of CPPGRD is measured using unfolding conditions for alcohol dehydrogenase and α‐lactalbumin. The antiapoptotic action of the peptide chaperone is evaluated using H2 O2 ‐induced Cos‐7 and ARPE‐19 cell apoptosis assays. The results show that the CPPGRD has both chaperone function and antiapoptotic activity. Additionally, the CPPGRD is found to prevent β‐amyloid fibril formation and suppress β‐amyloid toxicity. The present study demonstrates that the CPPGRD protects unfolding proteins from aggregation and prevents cellular apoptosis. Therefore, the CPPGRD is a minichaperone with potential to become a therapeutic agent for protein aggregation diseases. Abstract : A peptide chaperone encapsulating the chaperone site of αA‐crystallin is developed to penetrate cells and control β‐Amyloid fibril formation and toxicity. In this study, the effects of the peptide on unfolding proteins and cells subjected to oxidative stress are investigated. In the presence of the peptide, suppression of unfolding protein aggregation and prevention of hydrogen peroxide‐induced cellular apoptosis are observed.